2010
DOI: 10.1093/jxb/erq076
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of five novel putative constitutive gene promoters in transgenic rice plants

Abstract: Novel constitutive gene promoters are essential components of crop biotechnology. Our analysis of five such promoters, APX, SCP1, PGD1, R1G1B, and EIF5, in transgenic rice plants is reported here. The five promoter regions were linked to the gfp reporter gene and transformed into rice. Using fluorescent microscopy and q-RT-PCR, promoter activities were analysed in comparison with OsCc1, Act1, and ZmUbi1, previously characterized as strong constitutive promoters. The APX and PGD1 promoters direct high levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
81
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(88 citation statements)
references
References 41 publications
2
81
0
5
Order By: Relevance
“…Although the CaMV 35S promoter has been shown to be active in most tissues of several plant species (26), in this research it was found to be the weakest of the promoters tested in sugarcane. While differences in transient gene expression level were observed among the monocot promoters, the highest activity was obtained with the Act1 promoter, which is in agreement with previous reports on the Act1-D promoter activity in other monocots such as date palm (16) and rice (27). In conclusion, the histochemical staining results indicated that the rice Act1 promoter is preferred for stable expression of foreign genes in sugarcane callus.…”
Section: Discussionsupporting
confidence: 91%
“…Although the CaMV 35S promoter has been shown to be active in most tissues of several plant species (26), in this research it was found to be the weakest of the promoters tested in sugarcane. While differences in transient gene expression level were observed among the monocot promoters, the highest activity was obtained with the Act1 promoter, which is in agreement with previous reports on the Act1-D promoter activity in other monocots such as date palm (16) and rice (27). In conclusion, the histochemical staining results indicated that the rice Act1 promoter is preferred for stable expression of foreign genes in sugarcane callus.…”
Section: Discussionsupporting
confidence: 91%
“…It has to be emphasized that promoters isolated from dicotyledonous plants are more efficient while used in dicots. The same rule applies for promoters isolated from monocots (Park et al 2010). Odell et al (1985) analyzed the sequence of constitutive promoter CaMV 35S , isolated from Cauliflower mosaic virus.…”
Section: Types Of Gene Promotersmentioning
confidence: 99%
“…Alike constitutive promoters, those obtained from monocots may not be equally active in dicots (and vice versa). Occasionally, application of promoter considered as specific may result in non-specific heterologous gene expression (Park et al 2010). For example, wheat transformation with glutenin promoter LMWG1D1 led to the efficient expression within the endosperm.…”
Section: Tissue-specific Promotersmentioning
confidence: 99%
See 1 more Smart Citation
“…Em plantas transgênicas de citros, o promotor constitutivo 35S, oriundo do vírus do mosaico da couve-flor (CaMV) é o mais utilizado nas construções gênicas (FAGOAGA et al, 2001;YANG et al, 2011;MUNIZ et al, 2012). Park et al (2010) mostraram ainda que, este promotor regula a expressão do transgene em níveis elevados.…”
Section: Lista De Tabelasunclassified